In vitro screening and in vivo colonization pilot model of Lactobacillus plantarum LP5 and Campylobacter coli DSPV 458 in mice - Ruiz, María Julia; Zbrun, María Virginia; Signorini Porchiett, Marcelo Lisandro; Zimmermann, Jorge Alberto; Soto, Lorena Paola; Rosmini, Marcelo Raúl; Frizzo, Laureano Sebastian (Springer, 2021)
The objective of this work was to determine the antibacterial effect of Lactobacillus plantarum strains of pork origin against Campylobacter coli strains, and to conduct experimental colonization pilot models in mice for both microorganisms. Inhibition assays allowed evaluation and selection of L. plantarum LP5 as the strain with the highest antagonistic activity against C. coli and with the best potential to be used in in vivo study. Adult 6-week-old female Balb/cCmedc mice were lodged in two groups. The treated group was administered with 9.4 log10CFU/2 times/wk of L. plantarum LP5. L. plantarum LP5 was recovered from the feces and cecum of the inoculated mice. However, when bacteria stopped being administered, probiotic counts decreased. Experimental colonization with C. coli was carried out in five groups of mice. All animals were treated with antibiotics in their drinking water to weaken the indigenous microbiota and to allow colonization of C. coli. Four groups were administered once with different C. coli strains (DSPV458: 8.49 log10CFU; DSPV567: 8.09 log10CFU; DSPV570: 8.46 log10CFU; DSPV541: 8.86 log10CFU, respectively). After 8 h, mice inoculated with different C. coli strains were colonized because the pathogen was detected in their feces. L. plantarum LP5 tolerated the gastrointestinal conditions of murine model without generating adverse effects on the animals. C. coli DSPV458 colonized the mice without causing infection by lodging in their digestive tract, thus generating a reproducible colonization model. Both models combined could be used as protection murine models against pathogens to test alternative control tools to antibiotics.